Redefining nursing from a Filipino perspective. - Rivera, Arnold F. (2011)
This study aimed to explore, describe and document the experiences of nurses in order to come up with a unique definition of nursing as experienced in the hospital setting. Using the phenomenological approach, specifically, the descriptive phenomenology of Husserl, this study described the lived experiences of twelve (12) full time staff nurses who saturated data in this research rigor. Purposeful sampling was utilized to select participants in four (4) tertiary general hospitals (government and private) in Manila, Philippines. An in-depth interview was used to generate data about the participant's personal and professional experiences' in nursing. The interviews were transcribed verbatim, and were analyzed and described using a descriptive phenomenological methodology. The three main themes that emerged were: (1) Nursing being defined as performing tasks that alternate between caring and using medical-technical approaches, (2) Nursing being defined as a health care profession, and (3) Nursing being defined within the boundaries of high cultural appraisal and challenged socio-institutional status. The findings have implications for nursing educators, administrators and leaders to create means to further enhance the caring attributes of Filipino nurses; to perform evaluation per institution to identify the specific needs of the nursing workforce and bring changes wherever deemed applicable that could improve nursing practice.
Keywords: NURSING; NURSING-PHILIPPINES.